STIMULATION GROWTH, YIELD, AND ACCUMILATION OF ANTIOXIDANT COMPOUNDS OF ONION HYBRIDS BY COLORED SHADES OF POLY ETHYLENE COVERS - Al-Khafaji, A. M. H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was conducted at vegetable field of the Department of Horticulture and Landscape Gardening –College of Agricultural Engineering Sciences - University of Baghdad. The experiment was conducted using Randomized Complete Block Design within split plot arrangement with three replicates. The hybrids (white, yellow, red) represented the main plots, symbolized (HW, HY, HR) and the colored covers of the tunnels (without cover, transparent, red, yellow, blue) represented the sub plots, which symbolized (C0, CW, CR, CY, CB).The statistical analysis revealed significant differences of HR in producing the highest values of the studied traits, such as, leaves number (14.73), leaf area (24.79 dcm2), plant yield (190 gm.), chlorophyll concentration (9.733 mg.100-1gm f. w.). Also the results revealed the significant superiority of yellow cover, in leaves number (18.11), leaf area (29.63 dcm2), plant yield (222 gm.), chlorophyll concentration (10.44 mg.100-1gm f. w.), anthocyanin concentration (24.67 mg.100-1gm f. w.). The results that obtained from interaction between hybrids and covers were showed the significant predomination of HRCY in producing the highest numbers in the mentioned characters (18.33 leaves, 34.18 dcm2, 233.3 gm. 11.33 mg.100-1gm f. w.) respectively.